The Assessment of Muscle Strength in Fracture Patients with Manual Muscle Testing: Narrative Literature Review - Hidayah, Nurul; Hakam, Mulia; Kushariyadi, Kushariyadi (Universitas Pendidikan Indonesia, 2021)
Introduction: Decreased muscle strength in fracture patients can be caused by postoperative immobilization, thus requiring early immobilization to accelerate the fracture healing process. The principle of early immobilization is the same as the assessment of muscle strength, namely flexion, extension, and rotation to determine muscle strength in fracture patients. Objectives: To determine the decrease in muscle strength with the Manual Muscle Testing (MMT) method in fractured and non-fractured patients. Methods: Narrative literature review was chosen in this research design. Literature search through seven databases with keywords using boolean operators and found 6533 articles. The selection process is based on several criteria: the publication year 2015-2020, full-text access, National (SINTA) / International (Scimagojr) indexed articles, in English or Indonesian, so that 11 articles were reviewed in this study. Results: MMT is a reliable measurement tool, does not require additional tools to assess muscle strength and is universal (can assess muscle strength in fractures and non-fractures). Discussion: MMT examination needs to be performed on fracture patients to determine muscle strength to accelerate the muscle recovery process.ABSTRAK Pendahuluan: Penurunan kekuatan otot pada pasien fraktur disebabkan imobilisasi post operasi, sehingga memerlukan early immobilization untuk mempercepat proses penyembuhan fraktur. Prinsip early immobilization sama dengan penilaian kekuatan otot yaitu melakukan fleksi, ekstensi, dan rotasi guna mengetahui kekuatan otot pada pasien fraktur. Tujuan: Untuk mengetahui adanya penurunan kekuatan otot dengan metode Manual Muscle Testing (MMT) pada pasien fraktur dan non fraktur. Metode:Narrative literature review dipilih dalam desain penelitian ini. Pencarian literatur melalui tujuh database dengan kata kunci menggunakan boolean operator dan ditemukan 6533 artikel. Proses seleksi berdasarkan beberapa kriteria: tahun publikasi 2015-2020, akses full text, artikel terindeks Nasional (SINTA)/Internasional (Scimagojr), berbahasa Inggris atau bahasa Indonesia, sehingga didapatkan sebanyak 11 artikel yang direview pada penelitian ini. Hasil : MMT merupakan alat ukur yang reliable, tidak memerlukan alat tambahan untuk melakukan penilaian kekuatan otot, dan universal (dapat menilai kekuatan otot pada fraktur maupun non fraktur). Diskusi : Pemeriksaan MMT perlu dilakukan pada pasien fraktur untuk mengetahui tingkat kekuatan otot sehingga mempercepat proses recovery otot.